(2-Chlorobenzoyloxy)copper(i) catalyzed C–S cross-coupling of di(hetero)aryl disulfides with aryl boronic acids under base-free conditions1. Issue 56 (19th June 2015) - Guo, Yan; Quan, Zheng-Jun; Da, Yu-Xia; Zhang, Zhang; Wang, Xi-Cun
<x xml:space="preserve">Abstract</x> (2-Chlorobenzoyloxy)copper(i) exhibited high activity towards the challenging C–S cross-coupling of di(hetero)aryl disulfides with aryl boric acids with good to excellent yields under base-free conditions.